Prototipe Pendeteksi Kebakaran Menggunakan NodeMCU ESP8266 Dengan implementasi Logika Fuzzy - Gagas Abdul Yasir; Fathia Frazna Az-Zahra (STEKOM PRESS, 2022)
Fires doesn’t know the place and time, they can happen anywhere and anytime. Some of the causes of fires are human error, electrical short circuit, cigarettes, stoves, etc. As a result, many parties suffered losses, both property, business entities, and casualties. Based on these problems, we need a system that is able to detect fires and take preventive action, namely notifications via the internet using the Blynk application. In this study, the parameters used are the temperature sensor, the MQ-2 smoke sensor and the flame sensor. The output of the system is a buzzer, LED, LCD, and Blynk app as notifications. The Fuzzy Logic method is applied to the system to control the Buzzer, LED, LCD and notification determinants to the Blynk application.